2020
DOI: 10.3390/agriculture10090406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Metabolomic Changes in Lettuce Leaves under Low Nitrogen and Phosphorus Deficiencies Stresses

Abstract: Nitrogen and phosphorus limitation affect the growth, development, and productivity of lettuce, which exert a marked influence on metabolites. To compare the influence of low-nitrogen and low-phosphorus stresses on various metabolites of lettuce leaves, experiments were performed under three conditions of treatment—low-nitrogen stress, low-phosphorus stress, and normal samples. Metabolomic analyses were conducted based on ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry. Prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Our current understanding of how the controlled manipulation of multiple mineral elements interacts on a pre-existing phytochemical diversity in plants is very limited, also because, for instance, different studies have been carried out in relation to an exposure to abiotic stress conditions [51][52][53][54]. The analysis of the effects on the NS in relation to the different colored genotypes provided interesting insights.…”
Section: Discussionmentioning
confidence: 99%
“…Our current understanding of how the controlled manipulation of multiple mineral elements interacts on a pre-existing phytochemical diversity in plants is very limited, also because, for instance, different studies have been carried out in relation to an exposure to abiotic stress conditions [51][52][53][54]. The analysis of the effects on the NS in relation to the different colored genotypes provided interesting insights.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al (2020) found that the levels of anti-stress substances and amino acid substitutes increased under N deficiency, and the metabolism of benzoic acid, erucic acid, and glucuronate in rice leaves was related to low-P stress. Gao et al (2020) found that p-hydroxybenzoic acid, inositol, dinol, and stachyose levels increased in lettuce leaves under N deficiency.…”
Section: Introductionmentioning
confidence: 94%
“…The treatment of low phosphorus stress was to reduce H 2 PO 4 − in nutrient solution to 0.3125, 0.625 and 0.9375 mmol•L −1 respectively; the treatment method of high phosphorus stress was to increase H 2 PO 4 − in nutrient solution to 1.875 mmol•L −1 . The greenhouse temperature ranged from 18-35 • C. The average daily irradiation was 13.2 MJ/m 2 , and the average natural light duration was 5.13 h. After two weeks, samples were taken between 10:00 and 12:00 am to minimize diurnal effects on metabolite concentration [5]. Qualitative and quantitative analysis was performed with GC-MS after the sampling was completed.…”
Section: Plant Sample Cultivationmentioning
confidence: 99%
“…However, before the external characteristics of plants change, in order to resist the harm caused by phosphorus stress, plants use their metabolic ability to produce a large number of small molecular compounds and restructure their metabolic network to maintain necessary metabolism. Therefore, at the molecular level, the method of detecting metabolic biomarkers can quickly and efficiently reflect whether the phosphorus nutrient supply level of plants is normal, and confirm the nutritional status of plants as soon as possible when the nutrient deficiency can still be remedied [5], and guide the reasonable fertilization scheme, which has great practical significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation